1992
DOI: 10.1007/bf01991224
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of neurally mediated airway microvascular leakage in guinea-pig airways byβ 2 agonists

Abstract: The effect of two beta 2-adrenoceptor agonists, salbutamol (100 micrograms/kg i.v.) and broxaterol (100 micrograms/kg i.v.), on airway microvascular leakage induced by vagal stimulation was studied in anaesthetised guinea pigs. Airway microvascular leakage was measured by Evans blue extravasation. Broxaterol, but not salbutamol, inhibited Evans blue dye extravasation at all airway levels, an effect prevented by pretreatment with propranolol (1 mg/kg). Neither of the beta 2-agonists had any effect on substance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…fl2-adrenoceptor agonists have been shown to attenuate airway microvascular leakage induced by various mediators such as histamine [3][4][5] and bradykinin [3,5,6]. In addition, inhibition of neurogenic-induced airway microvascular leakage has been reported [3,7,8]. The effect of fl2-adrenoceptor agonists in preventing bronchoconstriction appears to be more potent than in reducing airway microvascular leakage as shown against histamine-induced effects [4].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…fl2-adrenoceptor agonists have been shown to attenuate airway microvascular leakage induced by various mediators such as histamine [3][4][5] and bradykinin [3,5,6]. In addition, inhibition of neurogenic-induced airway microvascular leakage has been reported [3,7,8]. The effect of fl2-adrenoceptor agonists in preventing bronchoconstriction appears to be more potent than in reducing airway microvascular leakage as shown against histamine-induced effects [4].…”
Section: Introductionmentioning
confidence: 89%
“…We chose the doses of formoterol and salbutamol as previously used in a study in our laboratory [4]. PAF at the dose of 1 mM (30 breaths) has been shown to induce significant submaximal extravasation of Evans blue dye at all airway levels [8].…”
Section: Measurement Of Airway Microvascular Leakagementioning
confidence: 99%
“…Salbutamol completely inhibited the UNDW-induced increase in the Pao. It has been shown that intravenously administered salbutamol does not inhibit airway microvascular leakage induced by vagal stimulation [21], substance P [21], or platelet-activating factor [22], and that it has little or no inhibitory effect on histamine-induced microvascular permeability in proximal and distal intrapulmonary airways [23]. Taken together, it is likely that the increase in Pao is indicative of bronchoconstriction induced by the inhalation of UNDW in our guinea-pig model.…”
Section: Discussionmentioning
confidence: 62%
“…Several mechanisms have been proposed for the anti-edema effects of 132 agonists. Amongthese mechanisms arethe inhibition of mastcell degranulation(6), a direct antipermeability action on the vascular endothelium (7), and the inhibition of inflammatory mediator release from sensory nerves (8,9).Formoterol is a new, potent, long-acting 132 agonistthat hasbeen shown to inhibit plasma extravasation in the airways caused by histamineand bradykinin (8, 10, 11), and by electrical stimulation …”
mentioning
confidence: 99%
“…Several mechanisms have been proposed for the anti-edema effects of 132 agonists. Amongthese mechanisms arethe inhibition of mastcell degranulation(6), a direct antipermeability action on the vascular endothelium (7), and the inhibition of inflammatory mediator release from sensory nerves (8,9).…”
mentioning
confidence: 99%